MEMBANGUN JIWA PEKA ( PRODUKTIF, EDUKATIF, KOOPERATIF DAN AKSI) DALAM MENDORONG PEMULIHAN MASA PANDEMI DI KOTA BATAM - Maya Richmayati; Hendri Herman; Elminaliya Sandra (ASOSIASI IDEBAHASA KEPRI, 2022)
The pandemic period is not completely over and there are more and more people who are economically disadvantaged and need help. There is a problem related to the distribution of necessities, where students cannot go directly to the field. Regarding the distribution of necessities, which is one of the sensitive issues, which is happening at this time in the Tanjung Uncang village. Some people promise cheap groceries, but they never come. Even though people have paid for it, people are afraid of it. The purpose of community service is to help people who have irregular incomes. The method used is social service by providing food packages to people in need .